Methods for Procedural Terrain Generation - Piispa, Kasimir (My University, 2022)
Procedural generation has been utilized in the automatic generation of data for a long time. This automated processing has been utilized in the entertainment industry as well as in research work in order to be able to quickly produce large amounts of just the kind of data needed, for example, in system testing. In this thesis, we examine different ways to utilize procedural generation to produce different synthetic terrains. First, we will take a closer look at what procedural generation is, where it originally started, and where it was utilized. From this we move on to look at how this technology is utilized in the creation of terrains and what terrain is generally visually required. From this we move on to look at different ways to implement terrain generation. As part of this thesis, we have selected three methods and implemented our own implementations for terrain generation. We look at the performance of these implementations, and what a test group thinks about those synthetic terrains. The results obtained from this are analyzed and presented at the end of the thesis.

Proseduraalista generointia on hyödynnetty datan automaattisessa tuottamisessa jo pitkään. Tätä automatisoitua prosessointia on niin hyödynnetty viihdeteollisuudessa kuin tutkimustyössä, jotta ollaan voitu tuottaa nopeasti suuria määriä juuri sellaista dataa kuin tarvitaan esimerkiksi järjestelmän testauksessa. Tässä tutkielmassa tarkastellaan erilaisia tapoja hyödyntää proseduraalista generointia erilaisten synteettisten maastojen tuottamiseksi. Aluksi tutustutaan hieman tarkemmin siihen mitä proseduraalinen generointi on, mistä se on alunperin lähtenyt ja mihin sitä on hyödynnetty. Tästä siirrytään tarkastelemaan miten kyseistä tekniikkaa hyödynnetään maastojen luomisessa ja mitä maastoilta yleensä visuaalisesti vaaditaan. Tästä siirrytään tarkastelemaan eri tapoja toteuttaa maaston generointia. Osana tätä tutkielmaa, on valittu kolme menetelmää ja laadittu niistä kullekin oma toteutus maaston generointiin. Työssä tarkastellaan näiden toteutusten suoritustuloksia, ja mitä mieltä testiryhmä on kyseisistä synteettisistä maastoista. Saadut tulokset ja niiden analyyysi esitellään tutkielman lopussa.
Keywords: procedural generation, automatic, landscape, terrain generation, virtual, methods